Fostering The Sense of Eco-Innovation Among Entrepreneurs - Ferdy Andrian; Kartika Nuringsih (Graduate Program of Universitas Tarumanagara, 2023)
In line with the target of achieving sustainable development goals in 2030, the sustainability issues must be the foundation for building a competitive advantage for the company. Likewise, for micro, small and medium enterprises (MSMEs) to apply sustainability aspects in building sustainable competitive advantages. Therefore, the research objective is to analyze various factors affecting the sustainability of the competitive advantage of MSMEs in West Jakarta. Based on a prior study, three variables were selected, namely eco-innovation, eco-regulation, and green product behavior as determinants for sustainable competitive advantage. As many as 100 MSMEs were selected as respondents using a purposive sampling technique. Data were collected based on a questionnaire with quantitative analysis techniques using structural regression. Data processing using Smart-PLS with the following results: eco-regulation and green product behavior have a significant influence on sustainable competitive advantages. The influence of the formation of competitive advantage by the two variables is well perceived by business actors. Otherwise, eco-innovation has no significant effect on the sustainability of competitive advantage. Therefore, it is necessary to educate MSMEs to foster a sense of eco- innovation among MSMEs to support a green economy which ultimately contributes to the achievement of sustainable development. In the end, the collaboration of three variables as a mechanism to build a sustainable competitive advantage.